Ethnobotany of traditional games in kapuas hulu regency as a source of biology learning - Mariska, Sonia; Sunandar, Ari; Rahayu, Hanum Mukti (JURNAL BIOEDUKATIKA, 2025)
Traditional games are a valuable resource for studying biology. Traditional games in Kapuas Hulu, such as bamboo toy guns (Dendrocalamus asper), wooden spinning tops, and necklace toys made from cassava stems (Manihot esculenta), illustrate how simple tools and plant-based materials are utilized in play activities. The purpose of this study is to identify the plants used in traditional games, the specific plant parts involved, and the potential of these games as learning tools for secondary and high school biology education. This research employs a qualitative descriptive method, including observation, interviews, and documentation. A total of 45 traditional games were examined, involving 29 different plant species. Bamboo (Dendrocalamus asper) and cassava (Manihot esculenta) were among the most frequently used plants in these games. The study found that traditional games hold high potential as biology learning resources, with a score of 99.47%.